Visual analysis of self-presentation of teenagers and emerging adults on Facebook - Nor, Nor Fariza Mohd; Fuat, Nur Hazirah Binti Mohd (Universitas Pendidikan Indonesia, 2021)
Facebook has become a worldwide phenomenon and is one of the greatest important means of communication between people. Given that teenagers and emerging adults are typically concerned with peer acceptance, physical appearance and the self-impressions they convey, they are active users of social networking sites (SNS) because these sites provide platforms for them to connect to their peers and facilitate identity construction and experimentation within a social context. The present study aims to address the gap about how teenagers and emerging adults in the Malaysian context present themselves by analysing the photos which they posted on Facebook and to examine online self-presentations in Facebook between teenager and emerging adults. A quantitative analysis (percentages of the representational and interactional meaning) and qualitative analysis was conducted on 200 images of teenagers and emerging adults, which were collected from 40 participants (5 images from each participant). The 40 participants who consisted of teenagers and emerging adults were selected based on gender, age, geographical location and Facebook access. Kress and van Leeuwen’s (1996, 2006) metafunctional framework was employed to analyse the photos. The results show that there are similarities and differences in terms of self-presentation. Teenagers and emerging adults posed differently, with regard to the shot, gaze and angle, the location of the photos, their actions in the photos, their position (position or placement of the participants in the photo) and the relation between the image background of the participants. This study also found that teenagers and emerging adults in Malaysia exhibit behaviors which can be considered universal based on the visual analysis of their online photos. An important contribution of this study is how culture and religion contribute to the types of photos and poses posted by both groups on Facebook.